A Coordenação na Gramática Discursivo-Funcional - Pezatti, Erotilde; Mackenzie, J. Lachlan (Linguistik Online, 2022)
Coordination has commonly been treated as a grammatical process of connecting clauses, in which an equipollence relation may occur between the units involved. The purpose of this paper is to show how a discourse-functional theory understands coordination, relating it to the levels and layers proposed in the model of Functional Discourse Grammar (Hengeveld/Mackenzie 2008). We propose that coordination in Portuguese, as a morphosyntactic phenomenon, results from the double action of the Interpersonal and Representational Levels: the relations of addition and alternativity (expressed by e and ou respectively) result not only from parallelism at the Interpersonal Level but also from operations at the Representational Level that make use of notions found in logic. The adversative relation expressed by mas, however, is shown to be identical to the additive one at the Representational Level, differing only at the Interpersonal Level, where it requires the rhetorical function Concession to be assigned to a dependent Discourse Act.